Monitoring of chimerism after allogeneic hematopoietic stem cell transplantation - D. S. Dubnyak; N. V. Risinskaya; M. Yu. Drokov; A. B. Sudarikov (Трансплантология (Москва))
Allogeneic hematopoietic stem cells transplantation is one of the effective methods of treating patients with diseases of the blood system.Establishment of complete (100%) donor chimerism is among of the main indicators of successful transplantation in such cases. Monitoring chimerism makes it possible both to assess the graft acceptance, and also potentially predict the risk of developing primary/secondary graft failure, relapse, and graft-versus-host disease.The purpose of this review is to summarize the main concepts associated with chimerism after allogeneic hematopoietic stem cell transplantation; consideration of the need to study chimerism in various cell populations, as well as the relationship between chimerism and the development of various immunological complications.